2021
DOI: 10.1111/josh.13025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School Nurse Ratios and Health Services on Selected Student Health and Education Outcomes: North Carolina, 2011‐2016

Abstract: Background Determination of adequate school nurse staffing is a complex process. School nurse‐to‐student ratios and the health services school nurses provide to students should be considered. The purpose of this study was to examine the impact of North Carolina school nurse‐to‐student ratios and school nurse health services on the health and education outcomes (eg, absences, grades, self‐management) of students receiving services for asthma and diabetes. Methods This study of all 115 school districts in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…The need to introduce the health professional in our educational system is proven as Spain has the second highest rate of early school absenteeism in the European Union and is also the second European country with the highest rate of childhood and youth obesity in Europe [ 32 , 33 ]. Thus, according to Best et al’s study, the presence of a school nurse in educational centers (with adequate ratios) improves academic results and healthy habits of students, and reduces school absenteeism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need to introduce the health professional in our educational system is proven as Spain has the second highest rate of early school absenteeism in the European Union and is also the second European country with the highest rate of childhood and youth obesity in Europe [ 32 , 33 ]. Thus, according to Best et al’s study, the presence of a school nurse in educational centers (with adequate ratios) improves academic results and healthy habits of students, and reduces school absenteeism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…School nurses can support this population by establishing an effective bond, listening carefully to their feelings and health needs, intervening early and continuously, in collaboration with the family, school and health services, based on comprehensive care 43 . Studies show that, from the perspective of the educational system, school nurses contribute to improve health, reduce absenteeism and improve student performance 44 . Hence, WHO supports the creation of school-based health centers as an important community resource to address the health needs of adolescents and increase their participation in health services 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Children experiencing symptoms of asthma frequently visit school nurses (Best et al, 2021). We know that children with asthma are at higher risk of anxiety/depression and that this comorbidity leads to less controlled asthma and increased healthcare use (Bardach et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disease management is a common priority for school nurses and asthma is in the forefront. A recent study of school nurses in North Carolina indicated that students received asthma related care more than 100,000 times annually (Best et al, 2021). Intervening with this student population to improve asthma knowledge and self-management behaviors could reduce the burden of nurse time spent on administering care to the student with asthma, decrease lost instructional time, and improve academic and health outcomes (Harris et al, 2019).…”
Section: Introductionmentioning
confidence: 99%